INCREASE IN EXECUTIVE FUNCTIONS FROM THE USE OF VIDEOS AND PEDAGOGICAL PROGRAMS AS A PROPOSAL FOR INTERVENTION WITH AUTISTS: A CASE STUDY - Mirandade Alvarenga Dias, Fabrizia; Barcelos da Silva, Cristiana; de Souza Cordeiro, Lilliany (LINKSCIENCEPLACE, 2026)
The objective of this study is to analyze the cognitive gains after the implementation of technological tools as instruments of neuropsychological and pedagogical interventions with a child with Autism Spectrum Disorder, level 1. For this purpose, the standardized and qualitative instruments of evaluation of the executive functions were used: Neuropsychological Cognitive Assessment - Attention and Executive Functions, along with the Memory Test "7 figures, 7 words", daily observations, Interventions, Recent Articles and Bibliographies. The data analyzed suggest that the application of interventions with the use of technology was favorable to the cognition of the individual under study, with an improvement in school performance and social skills. It is important for practitioners to deepen and develop knowledge about methods and strategies with the use of mental health technology in order to increase their use in interventions with these children, assessing their effects.